A Analisis Postur Kerja Untuk Mengurangi Risiko Muskulokeletal Menggunakan Metode REBA Pada Operator Produksi Di PT XYZ - Aditya Jajang Nurzaman; Dene Herwanto; Wahyudin Wahyudin (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2020)
PT XYZ is a company of a motorcycle component and equipment industry group. PT XYZ produces motor brake brackets which will be sent to HONDA and YAMAHA. This study aims to evaluate the work posture of workers at the bending station with the Rapid Entire Body Assessment (REBA) method and propose an improvement to minimize the risk of injury due to fatigue. In the bending process, there are 3 main activities, namely: object retrieval, object installation, and bending process. The results of calculation with the REBA method before improvement showed a high level of risk from each activity, namely a score of 8 for the first activity, a score of 5 for the second activity, and a score of 7 for the third activity. After the improvement, a lower average score is obtained, which is equal to 3, which includes a low-risk level of risk. Improvement of work posture is done by designing work aids in the form of work desks and work chairs Work tools that have been made can help workers to help improve their work posture in carrying out work activities, so as to minimize the risk of injury.